A Proline-Based Tectons and Supramolecular Synthons for Drug Design 2.0: A Case Study of ACEI - Joanna Bojarska (Pharmaceuticals, 2020)
Proline is a unique, endogenous amino acid, prevalent in proteins and essential for living organisms. It is appreciated as a tecton for the rational design of new bio-active substances. Herein, we present a short overview of the subject. We analyzed 2366 proline-derived structures deposited in the Cambridge Structure Database, with emphasis on the angiotensin-converting enzyme inhibitors. The latter are the first-line antihypertensive and cardiological drugs. Their side effects prompt a search for improved pharmaceuticals. Characterization of tectons (molecular building blocks) and the resulting supramolecular synthons (patterns of intermolecular interactions) involving proline derivatives, as presented in this study, may be useful for in silico molecular docking and macromolecular modeling studies. The DFT, Hirshfeld surface and energy framework methods gave considerable insight into the nature of close inter-contacts and supramolecular topology. Substituents of proline entity are important for the formation and cooperation of synthons. Tectonic subunits contain proline moieties characterized by diverse ionization states: -N and -COOH(-COO−), -N+ and -COOH(-COO−), -NH and -COOH(-COO−), -NH+ and -COOH(-COO−), and -NH2+ and -COOH(-COO−). Furthermore, pharmacological profiles of ACE inhibitors and their impurities were determined via an in silico approach. The above data were used to develop comprehensive classification, which may be useful in further drug design studies.